Islamic Culture In The Umayyah Age II In Andalusia - Suchi Nurul Khofifah; Haidar Putra Daulay; Sholihah Titin Sumanti (Sean Institute, 2024)
The history of Islam in Spain, especially the Umayyad Dynasty II, is divided into five periods. The first period in 756-91 AD. Led by Caliph Abdurrahman I. The second period in 912-1013 AD. Led by Caliph Hisham, the third period in 1013-1086 AD, led by Caliph Hakam I, the fourth period in 1086-1248 AD. Led by Caliph Muhammad I. The policies of Caliph Hakam II were to hold religious ceremonies strictly and implement the teachings of the Sunnah throughout the territory of the Umayyad Dynasty II, the construction of General Hospitals, Housing Facilities, Transportation resources, maintaining peace and tolerance. War events also occurred during the time of Caliph Hakam II with the incident of Christians starting to rise up to carry out resistance movements against the power of the Umayyad Dynasty II. However, the progress of the Umayyad Dynasty during the time of Caliph Hakam II was also famous for its development of knowledge and culture, its love of literature and knowledge and its indulgence in the intellectuals.